V. M. Bekhterev in Russian child science, 1900s-1920s : “objective psychology”/“reflexology” as a scientific movement - Byford, Andy (Journal of the history of the behavioral sciences, 2016)
In the early 20th century the child population became a major focus of scientific, professional and public interest. This led to the crystallization of a dynamic field of child science, encompassing developmental and educational psychology, child psychiatry and special education, school hygiene and mental testing, juvenile criminology and the anthropology of childhood. This article discusses the role played in child science by the eminent Russian neurologist and psychiatrist Vladimir Mikhailovich Bekhterev. The latter's name is associated with a distinctive program for transforming the human sciences in general and psychology in particular that he in the 1900s labelled “objective psychology” and from the 1910s renamed “reflexology.” The article examines the equivocal place that Bekhterev's “objective psychology” and “reflexology” occupied in Russian/Soviet child science in the first three decades of the 20th century. While Bekhterev's prominence in this field is beyond doubt, analysis shows that “objective psychology” and “reflexology” had much less success in mobilizing support within it than certain other movements in this arena (for example, “experimental pedagogy” in the pre-revolutionary era); it also found it difficult to compete with the variety of rival programs that arose within Soviet “pedology” during the 1920s. However, this article also demonstrates that the study of child development played a pivotal role in Bekhterev's program for the transformation of the human sciences: it was especially important to his efforts to ground in empirical phenomena and in concrete research practices a new ontology of the psychological, which, the article argues, underpinned “objective psychology”/“reflexology” as a transformative scientific movement